Perilaku Kerja Inovatif Pegawai Negeri Sipil: Pengaruh Regulatory Focus, Inclusive Leadership dan Perceived Organizational Support yang dimediasi oleh Work Engagement - Hidayat, Apritama Nur; Prabawa, Made Andre Arya; M Eta, Yuli Safriah; Satrya, Aryana (UI Scholars Hub, 2023)
Indonesia's ranking in the 2021 Global Innovation Index, which ranks 87th out of 132 countries, shows that efforts to increase innovation are still needed. Various Ministries in Indonesia annually hold innovation competitions for the units under them to encourage quality improvement and familiarize the best practice culture for public service providers. This study aims to analyze the effect of regulatory focus, inclusive leadership, and perceived organizational support on innovative work behavior of employees at the Head Office of the Directorate General of Revenue (DGT) mediated by work engagement. The data collection method used a questionnaire given to 308 respondents online and processed using Structural Equation Modeling. The results of the study show that Promotion Focus, Prevention Focus, and Perceived Organizational Support have a positive effect on Work Engagement. Work Engagement also mediates these three variables on Innovation Work Behavior. However, Inclusive Leadership has no effect on Work Engagement nor is it mediated by Work Engagement onInnovation Work Behavior.